1994
DOI: 10.1002/gcc.2870090102
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic findings in malignant triton tumor

Abstract: Malignant triton tumor is a rare histologic variant of malignant schwannoma that shows both neural and skeletal muscle differentiation. In this study, cytogenetic analysis of a recurrent malignant triton tumor of the forearm from a 26-year-old female and a primary paraspinal malignant triton tumor from a 27-year-old female revealed complex karyotypes displaying multiple numerical and structural abnormalities. Abnormalities shared by both tumors included three copies of chromosome 22 and structural rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…The translocation (X;18) has apparently escaped detection in most, but not all (51), of the limited number of MPNST karyotypes reported to date, which have shown an inconsistent and remarkably complex array of cytogenetic abnormalities (55)(56)(57)(58)(59). Discrepancies between the results of standard cytogenetic analysis and RT-PCR have, however, been demonstrated for t(X;18).…”
Section: Discussionmentioning
confidence: 99%
“…The translocation (X;18) has apparently escaped detection in most, but not all (51), of the limited number of MPNST karyotypes reported to date, which have shown an inconsistent and remarkably complex array of cytogenetic abnormalities (55)(56)(57)(58)(59). Discrepancies between the results of standard cytogenetic analysis and RT-PCR have, however, been demonstrated for t(X;18).…”
Section: Discussionmentioning
confidence: 99%
“…Karyotypic studies 103,162,277,283 and three SKY studies 39,96,155 have revealed that these tumors possess karyotypic characteristics similar to malignant schwannomas. In most cases, structural aberrations involved chromosomes 7, 8, 17, and 22.…”
Section: Tumors Of Cranial and Spinal Nervesmentioning
confidence: 99%
“…A literature review using Medline was performed to find reports of cytogenetic studies of MPNSTs and 44 cases, including 4 malignant triton tumors, with abnormal karyotypes were found (Jhanwar et al, 1994;Sciot et al, 1995;Rao et al, 1996;Travis et al, 1994;McComb et al, 1996;Mertens et al, 1995a,b;Orndal et al, 1994;Rey et al, 1993;Fletcher et al, 1991;Glover et al, 1991;Decker et al, 1990;Riccardi and Elder, 1986;Becher et al, 1984). The patients comprised 20 males and 24 females ranging in age from 2 to 82 years; 25 were reported to have a history of neurofibromatosis type-1, while the NF-1 status of 9 patients was unclear.…”
Section: Methodsmentioning
confidence: 99%
“…Relative loss of chromosomal material in NF-1-associated MPNSTs as compared with sporadic MPNSTs was found in 1p3, 4p1 and 21p1-q2. Relative loss of chromosomal material in sporadic MPNSTs as Glover et al (1991) 1 1 ND Not reported Rey et al (1993) 1 1 ND Uncertain Jhanwar et al (1994) 10 9 ϩ 2 Not reported Orndal et al (1994) 1 1 ϩ Not reported Travis et al (1994) 2 0 ϩ Not reported Mertens et al (1995a) 1 ? ϩ Not reported Mertens et al (1995b) 7 4 ϩ Not reported Sciot et al (1995) 1 ?…”
Section: Nf-1-associated Vs Sporadic Mpnstsmentioning
confidence: 99%
See 1 more Smart Citation